2005
DOI: 10.1177/112067210501500312
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Extracellular Matrix Components in Epiretinal Membranes of Vitreoproliferative Retinopathy and Proliferative Diabetic Retinopathy

Abstract: The results indicated that the extracellular matrix components seem to be involved in PVR and PDR, contributing to tissue remodeling and perhaps by different pathogenetic pathways, which could reflect different stages of development in these two types of membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 34 publications
2
25
1
3
Order By: Relevance
“…Studies on cultured RPE cells have shown that they attach to and spread on individual matrix molecules, such as collagen [2] , laminin [3,4] and fibronectin (FN) [5] . In early stages of PVR, the provisional extracellular matrix (ECM) is synthesized locally by several cell types including RPE cells [6] . RPE cells interact with the ECM, migrate and proliferate.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cultured RPE cells have shown that they attach to and spread on individual matrix molecules, such as collagen [2] , laminin [3,4] and fibronectin (FN) [5] . In early stages of PVR, the provisional extracellular matrix (ECM) is synthesized locally by several cell types including RPE cells [6] . RPE cells interact with the ECM, migrate and proliferate.…”
Section: Introductionmentioning
confidence: 99%
“…The membranes also contained many areas that were not labelled with any of the antibodies used in this study. Presumably these areas contain mostly extracellular matrix components,79 but the neurites were not observed growing on these surfaces. Since the ILM often adheres to the ERMs when they are peeled from the retina, we stained with anti-laminin to see if the ILM could act as a substrate for neurite growth.…”
Section: Resultsmentioning
confidence: 98%
“…Retinal pigment epithelial cells have not been found to be part of the cellular population in idiopathic ERMs 5. The extracellular matrix components that have been identified in ERMs include actin, tenascin, fibronectin, laminin and collagen type I, III and IV in variable quantities 79…”
mentioning
confidence: 99%
“…In addition, our previous study revealed that hyalocytes and BRPEs could also be the sources of CTGF (13), and fibronectin is indicated to be a major component of the extracellular matrix proteins observed in epiretinal membranes of PDR and PVR (25). Taken together, CTGF secreted by hyalocytes and RPEs might modulate the formation of proliferative fibrous membrane in an autocrine and paracrine manner in the pathogenesis of proliferative vitreoretinal diseases, such as PDR and PVR.…”
Section: Discussionmentioning
confidence: 95%